The Pooling and Tranching of Securities: A Model of Informed Intermediation - DeMarzo, Peter M. (Review of Financial Studies, 2005)
I show that when an issuer has superior information about the value of its assets, it is better off selling assets separately rather than as a pool due to the information destruction effect of pooling. If, however, the issuer can create a derivative security that is collateralized by the assets, pooling and “tranching” may be optimal. If the residual risk of each asset is not highly correlated, tranching allows the issuer to exploit the risk diversification effect of pooling to create a low-risk and highly liquid security. In contrast, for an uninformed seller, pure pooling reduces underpricing and is preferred to separate asset sales. These results lead to a dynamic model of financial intermediation: originators sell pools of assets, some of which are purchased by informed intermediaries who then further pool and tranche them. Pooling and tranching allow intermediaries to leverage their capital more efficiently, enhancing the returns to their private information.